Controle de temperatura e umidade para um gabinete responsável pela transmissão de internet via rádio sujeito a intempéries - Gorte, Rodrigo (2012)
This paper presents the implementation of a temperature and humidity controller system using a microcontroller in order to control the temperature and the humidity in enclosures that houses wireless Internet network equipment aiming to prevent them to being damaged by weather conditions. The system consists of a microcontroller system with temperature and humidity sensors, two exhausters, a fan and a dehumidification resistance. A cabinet adding the proposed system was assembled to carry laboratory and field tests.